Direct Numerical Simulations of Self-Sustained Oscillations in Two-Dimensional Open Cavity for Subsonic and Supersonic Flow (Advances in Applied Mathematics and Mechanics, 2021)
Direct numerical simulations of self-sustained oscillations in two-dimensional rectangular cavity were performed in both subsonic and supersonic flow. A fifth order weighted essentially non-oscillatory (WENO) scheme was used for the nonlinear term of the two-dimensional unsteady compressible Navier-Stokes equations. A third order Runge-Kutta method was used to discretize the time derivative. The pressure signals on the cavity wall were analyzed by the short time Fourier transform (STFT) method. The formation mechanism of the component with lower frequency for the subsonic cases was analyzed. The detailed oscillating structures in and above the cavity were identified and the interactions between different waves were discussed for both the subsonic and supersonic cases. The results show the oscillating system would finally reach to the self-sustained state. The switching phenomenon of two waves in the cavity was identified for the supersonic case. An improved model of the shock wave patterns for supersonic case was given.